Niche conservatism constrains Australian honeyeater assemblages in stressful environments. (15th July 2013) - Miller, E. T.; Zanne, A. E.; Ricklefs, R. E.
Abstract: The hypothesis of phylogenetic niche conservatism proposes that most extant members of a clade remain in ancestral environments because expansion into new ecological space imposes a selectional load on a population. A prediction that follows is that local assemblages contain increasingly phylogenetically clustered subsets of species with increasing difference from the ancestral environment of a clade. We test this in Australian Meliphagidae, a continental radiation of birds that originated in wet, subtropical environments, but subsequently spread to drier environments as Australia became more arid during the late Cenozoic. We find local assemblages are increasingly phylogenetically clustered along a gradient of decreasing precipitation. The pattern is less clear along a temperature gradient. We develop a novel phyloclimatespace to visualise the expansion of some lineages into drier habitats. Although few species extend into arid regions, those that do occupy larger ranges and thus local species richness does not decline predictably with precipitation.